Survival of the fittest: qualitative and observational investigation of long-term happy marriages - Kılıç, Ezgi (İstanbul Bilgi Üniversitesi, 2021)
ABSTRACT: This thesis investigates the experiences and interactions of happy couples who were married at least ten years and having at least one child. Both thematic analysis and observational method of SCID were used to understand the experiences of these couples. While all eight couples participated in in-depth semi-structured interviews, interactions of only seven couples were analyzed through the observational method. The duration of marriage ranged between 12 to 24 years with a mean of 18, while the relationship's longevity ranged between 14 to 32 years with a mean of 23. The participants' mean age was 46, varying between 38 and 59. While six couples had two children, two of them had only one child. The individual and couple interviews, which approximately took 45 minutes each, were conducted in participants' houses. Qualitative findings unraveled common factors and experiences contributing to happy romantic relationships in long-term marriages. The interviews covered information regarding perceptions of the marriage, partners' contributions for marital happiness, faced challenges, coping mechanisms, relationships with parents, parents' relationship, and unique qualities of their relationship. With the combined analysis method, qualitative findings were supported with observational data regarding patterns of couple interaction, communication strategies, and relational positions of longstanding happy marriages. The results showed that establishing a good balance of individuality and togetherness in marriage and with others, appreciating positive aspects, and adopting constructive communication strategies contributed to the improvement of these couples' relationships over the years. The results provided insightful information for the couple therapists about the factors behind a satisfying couple relationship and marital stability. The findings are discussed in the light of existing literature as well as limitations and suggestions for further studies presented.

ÖZET: Bu çalışmada en az on yıllık evli ve en az bir çocuğu olan mutlu çiftlerin deneyimlerini ve etkileşimlerini incelemiştir. Bu çiftlerin deneyimlerini anlamak için tematik analiz ve gözlem yöntemi olarak SCID kullanılmıştır. Sekiz çiftin tamamı yarı yapılandırılmış görüşmelere katılırken, sadece yedi çiftin etkileşimleri gözlemsel yöntemle analiz edilmiştir. Ortalama 18 yıl olan evlilik süresi 12-24 yıl arasında değişirken, ilişkinin süresi 23 yıl ortalamayla 14 ile 32 yıl arasında değişmektedir. Katılımcıların yaş ortalaması 46 olup, yaşları 38 ile 59 arasında değişmektedir. Tek çocuk sahibi 2 çift haricindeki tüm çiftlerin 2 çocuğu bulunmaktadır. Her biri yaklaşık 45 dakika süren bireysel ve çift görüşmeleri katılımcıların evinde gerçekleştirilmiştir. Nitel bulgular, uzun süreli evliliklerde mutlu romantik ilişkilere katkıda bulunan ortak faktörleri ve deneyimleri ortaya çıkarmıştır. Görüşmelerin içeriği katılımcıların evlilik algıları, partnerlerin evlilik mutluluğuna katkıları, karşılaşılan zorluklar, başa çıkma mekanizmaları, ebeveynlerle ilişkiler, ebeveynlerin ilişkileri ve ilişkinin benzersiz nitelikleri ile ilgili bilgileri kapsamıştır. Nitel bulgular uzun süredir devam eden mutlu evliliklerdeki çift etkileşimi örüntüleri, iletişim stratejileri ve ilişkisel konumlarına ilişkin gözlemsel verilerle desteklenmiştir. Sonuçlar bu çiftlerin birbirleriyle ve başkalarıyla ilişkide bireysellik ve birliktelik dengesini iyi kurduğunu, var olan olumlu özelliklerin kıymetini bildiğini, yapıcı iletişim stratejilerini benimsediklerini ve böylece ilişkilerinin yıllar içerisinde daha da iyiye gittiğini göstermiştir. Bulgular tatmin edici bir çift ilişkisinin ardındaki faktörler ve evlilik istikrarı hakkında çift terapistlerine faydalı bilgiler sunmaktadır. Sonuçlar mevcut literatür ışığında tartışılmış, kısıtlamalar ve gelecek çalışmalar için öneriler sunulmuştur.
Sag? Kalan En I?yi Uyum Sag?layandır: Uzun Su?reli Mutlu Evliliklerin Nitel ve Go?zlemsel I?ncelemesi
Keywords: Mutlu Evlilikler; Evlilik Sürekliliği; Çift İlişkisi; Çift Etkileşimi; Tematik Analiz; Happy Marriages; Marital Stability; Couple Relationship; Couple Interaction; Thematic Analysis